Se debe incorporar en la ley de mediación y arbitraje, la conciliación familiar como una forma de resolver los conflictos familiares - Romero Pinela, Ángel Leonardo (2014)
Family conflicts are inherent and natural in our lives and in our relationships, however, rarely grasp the full depth of this truth; on the contrary, when we are faced with a conflict usually see as wrong, harmful and destructive, rather than understood as a form of interaction between people with positive or negative consequences, depending on how it is handled or resolved between the parties involved. This research is titled: "BE INCORPORATED IN THE LAW OF MEDIATION AND ARBITRATION SETTLEMENT THE FAMILY AS A WAY TO SOLVE FAMILY CONFLICT". One that addresses the problems associated lack of regulations in the Act of Mediation and Arbitration, in relation to the settlement for married couples who are divorcing. The hypothesis that I lead is you work research was: "The lack of regulation in the Law on Mediation and Arbitration, family mediation, in order to solve the problem in the marriage that are supporting various difficulties of family life." The processes used were hypothetical, inductive - deductive method, analytical explanatory, statistical; for the preparation of the descriptive analysis method was used. The techniques were applied was the survey of 30 practitioners in the free exercise of the city of Loja, through the instrument consisted of a series of questions designed to obtain relevant information. Among the outstanding results we have through the study and legal and legal analysis of the issues raised, it is shown that there are flaws in the law, the Law on Mediation and Arbitration, which contributes to mediate or resolve various family problems, what you need to modify or update the Act, in order to help resolve family conflicts.